The Effect Of Tele Education On Increasing The Self-Efficacy Of Pregnant Women In Sumatera Barat Province - Diana Putri (International Journal of Public Health, 2024)
Self-confidence is built by knowledge obtained through an accessible educational process, one of which is through tele-education. The treatment given was in the form of education using the whatsapps (WA) application in group forums for classical education and private lines for personal counseling sessions. The research population is all pregnant women in Indonesia. The sample was selected using a convenience sampling technique. A total of 53 subjects were obtained through online media based on inclusion criteria, including: 28-39 weeks of gestation, declared their ability to participate in the tele-education program using the WhatsApps application, and had an active WhatsApps account. The self-efficacy of pregnant women was measured using the Chilbirth Self-Efficacy Inventory (CBSEI) questionnaire presented before and after the intervention. Data were analyzed using Paired T-Test. Most of the respondents were aged 31-35 years, housewives, had high school and university education, and were pregnant for the first time. Analysis test to get sig. (2-tailed) of 0.004 <0.05, and the value of tcount is greater than ttable (3.067> 2.098). Tele education affects the self-efficacy of pregnant women in facing childbirth.